Flavonoids as natural anti-inflammatory agents targeting nuclear factor-kappa B (NFκB) signalling in cardiovascular diseases: a mini review - Choy, Ker Woon; Murugan, Dharmani; Leong, Xin Fang; Abas, Razif; Alias, Aspalilah; Mustafa, Mohd Rais (Frontiers Research Foundation, 2019)
Cardiovascular diseases (CVDs) such as angina, hypertension, myocardial ischemia, and heart failure are the leading causes of morbidity and mortality worldwide. One of the major transcription factors widely associated with CVDs is nuclear factor-kappa B (NFκB). NFκB activation initiates the canonical and non-conical pathways that promotes activation of transcription factors leading to inflammation, such as leukocyte adhesion molecules, cytokines, and chemokines. Flavonoids are bioactive polyphenolic compounds found abundantly in various fruits, vegetables, beverages (tea, coffee), nuts, and cereal products with cardiovascular protective properties. Flavonoids can be classified into six subgroups based on their chemical structures: flavanones, flavones, flavonols, flavan-3-ols, isoflavones, and anthocyanidins. As NFκB inhibitors, these flavonoids may modulate the expression of pro-inflammatory genes leading to the attenuation of the inflammatory responses underlying various cardiovascular pathology. This review presents an update on the anti-inflammatory actions of flavonoids via inhibition of NFκB mechanism supporting the therapeutic potential of these natural compounds in various CVDs.